1986
DOI: 10.1002/ajh.2830230104
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Rh antigens increase with red cell age

Abstract: Certain blood group antigens may play a role in the removal of senescent red cells from the circulation. In order to elucidate this hypothesis, we have investigated the effect of red cell aging on Rh blood group antigens. Red cells from volunteer donors were separated into subpopulations of uniformly defined densities on discontinuous Stractan density gradients. The number of the five major Rh antigen sites of each fraction was determined both by enzyme-linked immunosorbent assay (ELISA) and by hemagglutinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…During the life span of a host erythrocyte receptors molecules on the surface are continuously lost or degraded and other receptors like senescence factors become exposed (Killmann, 1964;Berlin and Berk, 1975;Ballas et al, 1986;Clark, 1988). This would mean to the merozoite that more mature erythrocytes have a potentially lower receptor density or contain receptors with reduced affinity.…”
Section: Discussionmentioning
confidence: 99%
“…During the life span of a host erythrocyte receptors molecules on the surface are continuously lost or degraded and other receptors like senescence factors become exposed (Killmann, 1964;Berlin and Berk, 1975;Ballas et al, 1986;Clark, 1988). This would mean to the merozoite that more mature erythrocytes have a potentially lower receptor density or contain receptors with reduced affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Accord ing to the hyothesis of membrane fluidity-dependent vertical translocation of mem brane proteins an increase in membrane ri gidity may enhance the exposure of mem brane proteins to the extramembranous en vironment [ 107], The observed increased ex posure of Rh antigens in older erythrocytes [108] could be explained by such a mecha nism (though other explanations are also possible). In the studies in which decrease in membrane fluidity was revealed, no signifi cant increase in the membrane cholesterol/ phospholipid ratio was found [45,46] so membrane rigidification has to be accounted for by other mechanisms.…”
Section: Membrane Organizationmentioning
confidence: 90%
“…If this were the case, then the predilection of different Plasmodium species to red blood cells of different ages (from reticulocytes to mature and possibly ageing normocytes) might well be accounted for by variations in the density of some receptors at the surface of the red blood cell. The fact that red blood cells are devoid of DNA does not preclude the appearance and increase of surface receptor as the red cell ages, as it is known that age-related alteration of the membrane leads to the exposure of some proteins that were inaccessible in the young red blood cell (Killmann, 1964;Berlin and Berk, 1975;Ballas et al, 1986;Clark, 1988;Woolley et al, 2000). However, experimental approaches that aim to elucidate the nature of the parasite's red blood cell tropism are actually quite restricted.…”
Section: Invasion Of Host Cells By Malaria Parasites 239mentioning
confidence: 99%